P162 Earlier (luminal) surgery is associated to reduced postoperative morbidity in ileocaecal Crohn's disease: results from SURGICROHN – LATAM study. (30th January 2023) - IBD Latam Consortium, S; Avellaneda, N L; Saddy Rodrigues Coy, C; Sarubbi Fillmann, H; Saad-Hossne, R; Muñoz, J P; García-Duperly, R; Bellolio, F; Rotholtz, N; Rossi, G; Marquez V, J R; Cillo, M; et al.
Abstract: Background: Early surgical resection is an emerging concept for patients with ileocaecal Crohn's disease (CD). The aim of this study was to compare postoperative outcomes after ileocaecal resections between patients with luminal and complicated CD. Methods: A retrospective analysis of patients operated for ileocaecal CD during an 8-year period in ten tertiary referral academic centres from Latin America was performed. Patients were allocated into 2 groups: those operated for early (luminal) disease (Early Crohn's Disease -ECD-) and for complications of CD (Complicated Crohn's disease -CCD-). A comparative analysis was performed regarding short-term outcomes of surgery, considering overall postoperative complications as main outcome. Results: 337 patients were included in the analysis, 60 (17.80%) in the ECD group. Smoking and exposure to perioperative biologic drugs were more prevalent in CCD group. CCD patients had increased requirement of urgent surgery (26.71 vs. 15%, p=0.056), longer operative time (164.25 vs. 90.53 minutes, p< 0.01), lower rates of primary anastomosis (90.23 vs. 100%, p=0.012), increased rate of overall postoperative complications (33.21 vs. 16.67%, p=0.013), more reoperations (13.36 vs. 3.33%, p=0.026), and higher rates of major anastomotic fistulas and hospital stay. On multivariable analysis, smoking (p= 0.001, 95%CI: 2.59-32.11), operative time (p=0.022, 95%CI:1-1.02), associated procedures (p=0.036, 95%CI:1.09-15.72) and intraoperative complications (p=0.021, 95%CI:1.45-92.31) were independently related to presenting postoperative complications. Conclusion: Early (luminal) ileocaecal resections were associated to lower rates of overall postoperative complications. Proper timing for surgery, avoiding delays in surgical indication can impact postoperative outcomes.